Supported Molybdenum Carbide and Nitride Catalysts for Carbon Dioxide Hydrogenation - Abou Hamdan, Marwa; Nassereddine, Abdallah; Checa, Ruben; Jahjah, Mohamad; Pinel, Catherine; Piccolo, Laurent; Perret, Noémie (Frontiers in Chemistry, 2020)
Catalysts based on molybdenum carbide or nitride nanoparticles (2-5 nm) supported on titania were prepared by wet-impregnation followed by a thermal treatment under alkane (methane or ethane)/hydrogen or nitrogen/hydrogen mixture, respectively. The samples were characterized by elemental analysis, volumetric adsorption of nitrogen, X-ray diffraction, and transmission electron microscopy. They were evaluated for the hydrogenation of CO2 in the 2-3 MPa and 200-300 °C ranges with a gas-phase flow fixed bed reactor. CO, methane, methanol, and ethane (in fraction-decreasing order) were formed on carbides, whereas CO, methanol, and methane were formed on nitrides. The carbide and nitride phase stoichiometries were tuned by varying the preparation conditions, leading to C/Mo and N/Mo atomic ratios of 0.2-1.8 and 0.5-0.7, respectively. The carbide activity increased for lower carburizing alkane concentration and temperature, i.e. lower C/Mo ratio. Enhanced carbide performances were obtained with pure anatase titania as compared to P25 (anatase/rutile) titania or zirconia as support, with a methanol selectivity up to 11% at 250 °C. The nitride catalysts appeared less active but reached a methanol selectivity of 16% at 250 °C.